Asymmetric Effect of Macroeconomic Variables on Rice Prices - Sri Herliana (AIBPM Publisher, 2023)
Rice price movements are basically influenced by movements in macroeconomic variables. This paper analyzes whether there is an asymmetric effect of macroeconomic variables on rice prices in Thailand as the largest rice exporter in ASEAN. In analyzing the asymmetric effects of macroeconomic variables (inflation and exchange rates) on rice prices in ASEAN countries, data on rice prices, exchange rates and inflation are used. This study focused on Thailand, one of the ASEAN exporting countries. The type of data used is monthly time series data with a time span of quarterly data from 2015Q1 to 2019Q1. The estimation evaluation results indicate that using a nonlinear model to examine the effect of inflation and the exchange rate on rice prices is preferable to using a linear model. The Wald's test estimation results in the short term show that for the NARDL model with asymmetric effects in the long and short term, Thailand has only a significant inflation variable while the Exchange Rate is not significant. Long- term Wald test estimation results show that the NARDL model in Thailand is not significant in all models.